Control of the postmating behavioral switch in Drosophila females by internal sensory neurons. - Yang, C.H.; Rumpf, S.; Xiang, Y.; Gordon, M.D.; Song, W.; Jan, L.Y.; Jan, Y.N. (Neuron, 2009)
Mating induces changes in the receptivity and egg-laying behavior in Drosophila females, primarily due to a peptide pheromone called sex peptide which is transferred with the sperm into the female reproductive tract during copulation. Whereas sex peptide is generally believed to modulate fruitless-GAL4-expressing neurons in the central nervous system to produce behavioral changes, we found that six to eight sensory neurons on the reproductive tract labeled by both ppk-GAL4 and fruitless-GAL4 can sense sex peptide to control the induction of postmating behaviors. In these sensory neurons, sex peptide appears to act through Pertussis toxin-sensitive G proteins and suppression of protein kinase A activity to reduce synaptic output. Our results uncover a neuronal mechanism by which sex peptide exerts its control over reproductive behaviors in Drosophila females.